Unveiling The Hidden Depths: A Deep Dive into Conversational Implicature In 'Lone Survivor' Directed by Peter Berg - Wahyu Utomo, Dhafid; Sidik , Ezis Japar; Mayasari, Jalia (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research delves into the nuanced world of conversational implicature, exploring the implied meanings and flouts of Grice’s cooperative principle in the film